(untitled) (Movimenta (ISSN 1984-4298), 2022)
Introduction: Cardiovascular diseases are among the main causes of mortality in Brazil, including coronary artery disease (CAD) the main cause of morbidity and mortality in Brazil, mainly affecting individuals of working age, generating a great economic impact. As an alternative to reduce symptoms and improve functionality and quality of life, cardiovascular rehabilitation (CR) based on supervised and well-prescribed physical exercises. Objective: to describe the result of a hybrid-strategy exercise-based CR program with a weekly supervised face-to-face visit and five days of unsupervised exercise prescription in a patient with CAD. Case report: Patient MRC 54 years old, male, brown, bricklayer, history of CAD, acute myocardial infarction, dyslipidemia and sedentary lifestyle. On assessment, she presented dyspnea on minimal exertion, with significant limitations in daily and professional activities. CR was proposed based on physical exercises 6 times a week, 5 times unsupervised and 1 time supervised, with moderate intensity for 30 minutes, for 6 months. Results: After 6 months, the patient presented a 6 mmHg decrease in SBP and an increase in HRV, representing an improvement in the health of the autonomic nervous system and cardiovascular, an increase of 5.83 ml/kg.min in V ̇O2 max, indicating an improvement in cardiorespiratory fitness and improvements in depression scores and quality of life. Conclusion: The hybrid CR strategy with emphasis on physical exercise for 6 months proved to be a viable alternative and with good therapeutic potential when performed according to prescriptions.